Electrorheological Response of Novel polyaniline-Fe2O3 Nanocomposite Particles. Issue 5 (24th March 2019) - Zhu, Xuyang; Zhao, Qing; Zhang, Ting; Pang, Xiufen
ABSTRACT: A novel polyaniline-Fe2 O3 (PANI-Fe2 O3 ) nanocomposite has been successfully prepared by oxidative in situ polymerization of aniline in the presence of iron nanoparticles. The characterization suggested the interactions between Fe2 O3 and PANI. The PANI-Fe2 O3 nanoparticles were used as a novel dispersed phase of electrorheological (ER) fluid and the evaluation results revealed that the yield stress of the new ER fluid can reach up to 10 kPa at 4.3 kV/mm, much higher than those of the ER fluids using PANI, Fe2 O3 or their mixture as dispersed phase, confirming that the interactions between Fe2 O3 and PANI are responsible for the high performance. GRAPHICAL ABSTRACT: